Newton loop method in gas pipeline network - Gindalan, Emma Olga Taimin (2010)
Pipeline networks are used extensively in all countries for transportation and distribution of natural gas and other light petroleum products for industrial and domestic use. However, one of the challenges of operating the pipeline network is how the operational procedures can be adjusted to meet the dynamic and future demands of customers. Thus, pipeline network simulation is an essential tool for control and operations in gas distribution systems because it can be used to stimulate and analyse networks behavior under different operating conditions. Analyses of pressures and flows are needed whenever significant changes in patterns and magnitudes of demand or supplies occur. Apart from that, there are many numerical methods that can be used in performing the gas pipeline network analysis. Thus, the hypothesis of the method states that the Newton Gauss Elimination method is faster and more accurate than the Newton Gauss Seidel method. The objectives of this research are to estimate the values of pressure drop of gas pipeline network by using Newton Loop method and to determine the accuracy and to compare the iteration number between Newton Gauss Elimination and Newton Gauss – Seidel. A case study was performed in low pressure and steady state condition. The case study covers the Gebeng Industrial Phase I and II only. FORTRAN program is developed to verify the manual calculation. Newton Gauss Elimination is more accurate than Newton Gauss – Seidel because Newton Gauss Elimination is a direct method while Newton Gauss – Seidel is an iterative method. This means Newton Gauss Elimination provides a straightforward solution while Newton Gauss – Seidel generates a sequence of successive approximation to the exact solution. The result from manual calculation and FORTRAN is approximately same.